The outcome of severely injured patients following traumatic brain injury is affected by gender—A retrospective, multicenter, matched-pair analysis utilizing data of the TraumaRegister DGU® - Olivia Mair; Frederik Greve; Rolf Lefering; Peter Biberthaler; Marc Hanschen; the TraumaRegister DGU (Frontiers in Neuroscience, 2022)
IntroductionTraumatic brain injury (TBI) causes a major health-concern globally. Gender-dependent differences in mortality outcome after TBI have been controversially discussed.Materials and methodsWe conducted a retrospective, multicenter, matched-pair analysis using data collected by the TraumaRegister DGU® of the German Trauma Society between 2009 and 2020. All patients after severe trauma with the leading injury of TBI (AIS ≥ 3), above 18 years of age were included. Thereby, 42,034 cases were identified. We used 12 different matching criteria to ensure highly accurate matching and were able to match 11,738 pairs of one female and one male patient.ResultsAverage age at injury was 67.5 ± 19.6 years in women and 66.7 ± 19.1 years in men. Mean Injury Severity Score (ISS) was 21.3 ± 8.1 in women and 21.6 ± 8.2 in men. While women were more likely to die within the first week after trauma, the mortality was significantly higher in men overall (30.8 vs. 29.2%, p < 0.002). Women were less likely to suffer from multi organ failure (MOF) (27.5 vs. 33.0%) or sepsis (4.5 vs. 7.1%). When comparing younger (≤ 45-years) and older (> 45 years) patients, overall mortality was lower in men (13.1% men vs. 13.4% women) in the younger age group, but in the older group mortality was lower in women (33.8% men vs. 31.8% women).DiscussionGender-specific differences in the clinical outcome of severely injured patients with leading TBI could be detected. While women are overall characterized by an advantage in survival, this feature is not equally reproducible in premenopausal women. Therefore, the exact pathophysiological reasons for the described survival advantages of women will have to be explored in further prospective clinical studies.